Propuesta de un plan de desarrollo turístico en la parroquia Nueva Loja, cantón Lago Agrio, provincia Sucumbíos. - Tipanluisa Portilla, Itaty Stephania (2022)
In the present research called "proposal for a tourism development plan in the parish of Nueva Loja", it has as its methodology the qualitative approach, developing different objectives, in such a way, journals, scientific articles, theses, PDYOT of the province and the canton were reviewed; for the fulfillment of the first, a situational diagnosis and the tourist system was made, where the local reality in which the parish was located was known, to know the demand of the place, the non-probabilistic method was applied for convenience, a survey was designed and it was applied to 60 people; as for the second Objective, field trips were made for the identification of the tourist attractions of the parish, each of them was visited to know their current state allowing the files to be filled using the methodology of Hierarchization of attractions and generation of tourist spaces in Ecuador, therefore, summaries of the cards were developed to know their content and according to the methodology give them a score and hierarchy as appropriate, key actors were identified through direct observation, to identify them an In Situ visit was made, where a talk was had with the tourism official and shared her point of View of tourism in the parish and its organization within it, based on it a table of problems was made, which allowed to know several tourist difficulties, so that, from this, the SWOT tool was used and internal and external factors evaluated from the previous problem table, likewise, a meeting was organized with the tourism department, where the SWOT was reviewed, since, thanks to its collaboration, 2030 as a tool that allowed to relate its strategic framework (axis, policies, objectives, strategies) in research, being a guide for the creation of the model of the action plan, in this way, axes were developed to establish the model of the plan, through programs and projects, these being able to design brands, create innovative products, disseminate tourism through technology, among others, classifying